PENYUSUNAN RENCANA INDUK PENGEMBANGAN KAWASAN RUMAH PANGAN LESTARI (KRPL) DI KAMPUNG SDGS BANGSALSARI KABUPATEN JEMBER - R. Abdoel Djamali; Getta Hayyuning Mangesti; Dhanang Eka Putra; Akhmad Suharto (Bajang Institute, 2022)
The dimensions of food security include four main components, namely: availability, access, use, and the purpose of this activity is to formulate and describe a plan for the development of a sustainable food house area in the SDG village, Bangsalsari district, Jember regency. The methods used are: field observation, FGD, and mentoring and training activities. The target audience for this activity are: Farmers and Young Farmers in Sukorejo Village, Bangdalsari District, Jember Regency. Conclusions from this activity: (a) a master plan for the development of KRPL in SDG Bangsalsari Village, Jember Regency has been successfully compiled which consists of: (1) Utilization of farmhouse yards for cultivation of vegetables and horticulture, and livestock and fisheries which are carried out independently and managed in one integrated management supports the success of the SDG program in Jember Regency, (2) the target of this activity and is committed to supporting and implementing the activity plans that have been jointly launched, (3) the need for operational funding support to implement an adequate and accountable KRPL plan under the assistance of the team Integrated College